IMPROVEMENT OF STUDENT WELLBEING OF STUDENTS THROUGH MOTIVATION INSTITUTIONS AT PONDOK PESANTREN NURUL JADID PAITON PROBOLINGGO - Muhammad Munif; Elok Fadilatur Rizqiyah; Siti Fatimah (Nurul Jadid University, 2021)
This study aims to determine the improvement of Student well-being of students through the Motivation Institute at Pondok Pesantren Nurul Jadid, and the implications of the guidance services provided by Lembaga Motivasi Nurul Jadid (LMNJ) on Student Wellbeing of students. This study uses a qualitative case study approach. Data collection techniques using observation, interviews, and documentation. The data analysis of this research went through three stages, namely data reduction, data display, and verification. The technique of checking the validity of the data is done by extending observations, increasing persistence, and triangulation. The results showed that to improve the Student Wellbeing of students at Pondok Pesantren Nurul Jadid, LMNJ used two methods, namely preventive and curative. Preventive services are carried out through socialization, seminars, discussions and religious lectures. Services that are curative are providing consulting services to students to solve problems related to psychology, social relations and learning. The implication of the guidance services provided by LMNJ to Student well-being of students is to create a sense of comfort for students, so that they can study well.